2014
DOI: 10.1093/ilar/ilu004
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Injuries in Elite Athletes: Lessons in Pathophysiology from Their Equine Counterparts

Abstract: Superficial digital flexor tendon (SDFT) injury in equine athletes is one of the most well-accepted, scientifically supported companion animal models of human disease (i.e., exerciseinduced Achilles tendon [AT] injury). The SDFT and AT are functionally and clinically equivalent (and important) energy-storing structures for which no equally appropriate rodent, rabbit, or other analogues exist. Access to equine tissues has facilitated significant advances in knowledge of tendon maturation and aging, determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 105 publications
(123 reference statements)
0
61
0
Order By: Relevance
“…Similar data are not available in humans. However, structural similarities between horses and human have been described in the literature (Kristoffersen et al., ; Patterson‐Kane et al., ; Patterson‐Kane & Rich, ). It is also important to note that the UTC method used in this study differs from the original articles (e.g., transducer moving automatically compared with moving manually, transducer captures over 12 cm compared with 9.6 cm, the region of tendon selected for quantification) (Rosengarten et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar data are not available in humans. However, structural similarities between horses and human have been described in the literature (Kristoffersen et al., ; Patterson‐Kane et al., ; Patterson‐Kane & Rich, ). It is also important to note that the UTC method used in this study differs from the original articles (e.g., transducer moving automatically compared with moving manually, transducer captures over 12 cm compared with 9.6 cm, the region of tendon selected for quantification) (Rosengarten et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The SDFT provides a good model for the human Achilles tendon, prone to aetiologically similar tendinopathies 47 , but is also a particularly highly loaded energy storing tendon 40 , providing an excellent structure-function model to study the structural mechanisms enabling the tendon to perform its mechanical function.…”
Section: Mechanical Functionmentioning
confidence: 99%
“…69 van Schie et al 95 scanned a cross-section of individuals with and without Achilles tendon pain and reported that the percentage of intact and aligned tendon bundles (echo type I) was reduced in the symptomatic tendon, with increases in echo types that represent disorganized structure (echo types III and IV). The ability to semi-quantify the structural integrity of the tendon has allowed for classification of the tendon pathology based on a continuum (FIGURE 7), treatment efficacy to be investigated, 21,23,24 detection of subtle changes in response to load, 29,79 and demonstration that the asymptomatic Achilles tendon is structurally compromised in individuals with unilateral tendon pain.…”
Section: New Imaging Modalitiesmentioning
confidence: 99%